2005
DOI: 10.1007/s10530-004-0952-8
|View full text |Cite
|
Sign up to set email alerts
|

Starting the invasion pathway: the interaction between source populations and human transport vectors

Abstract: Human transport hubs, such as shipping ports, airports and mail centers are important foci for the spread of non-indigenous species. High relative abundance in a transport hub has been proposed as a correlate of invasion success, since abundant species are thought more likely to colonize vectors and to be transported more frequently. We here evaluate the relative importance of vector characteristics and local source assemblages in determining the pool of species that is transported by hull fouling on recreatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(103 citation statements)
references
References 49 publications
2
101
0
Order By: Relevance
“…This pattern coincides with many other studies on artificial substrates (e.g. Davis et al, 1982;French and Livesey, 2000;Bustamante et al, 2007). In our study, some species were present on the groynes in high abundances such as B. ligerica which is also found in other Wadden Sea estuaries (cf.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This pattern coincides with many other studies on artificial substrates (e.g. Davis et al, 1982;French and Livesey, 2000;Bustamante et al, 2007). In our study, some species were present on the groynes in high abundances such as B. ligerica which is also found in other Wadden Sea estuaries (cf.…”
Section: Discussionsupporting
confidence: 93%
“…When nonindigenous species (NIS) occur on artificial structures (Ruiz et al, 2009;Glasby et al, 2007;Tyrrell and Byers, 2007;Wasson et al, 2005) these substrates may serve as stepping stones for invasive alien species (Apte et al, 2000;Wilhelmsson and Malm, 2008). Commercial ports and recreational marinas therefore provide the first habitats in a colonization corridor for introduced species (Floerl and Inglis, 2005;Bulleri and Airoldi, 2005). However, artificial substrates were also found to present refuges for endangered species of crustaceans (Krone and Schröder, 2011) or limpets (García-Gómez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that paint age can have a significant influence on biofouling communities, with older paint allowing the establishment of greater quantities of fouling. 119 Unpainted surfaces, such as those that evade actual paint coverage, eg, regions covered by support frames whilst the vessel is in dry dock and niche areas such as the propeller shaft, may allow sufficient area to facilitate biofouling. 120 In addition, minor failures (,0.5 cm wide) in the anti-fouling system, as a result of accidental damage during daily operations (eg, anchor damage, vessel groundings or minor collisions) can also lead to the rapid establishment of fouling species, including NIS on the unprotected areas.…”
Section: Anti-fouling Systemsmentioning
confidence: 99%
“…A recent study of Elkhorn Slough, California, revealed the presence of numerous invasive taxa present elsewhere along the west coast, despite the absence of any commercial ports (Wasson et al 2001), and fouling of recreational boats is probably a major vector for the movement of species between such habitats (Floerl & Inglis 2005). Fouling has been implicated in the global expansion of numerous invasive taxa, including crustaceans (Zardus & Hadfield 2005, Otani et al 2007), bryozoans (Marchini et al 2007), mollusks (Ricciardi 1998) and tunicates (Bullard et al 2007).…”
Section: Dispersal and Range Expansion Of Nematostella Vectensismentioning
confidence: 99%
“…A substantial proportion of these invasions have occurred in estuarine ecosystems, largely due to their association with common vectors of introduction such as commercial shipping and recreational boating , Carlton 2001, Floerl & Inglis 2005. The ecological consequences of estuarine invasions can be substantial (Grosholz 2002), and the associated costs in terms of lost ecosystem services may require significant investment in the management of threats posed by introduced populations (Williams & Grosholz 2008).…”
Section: Introductionmentioning
confidence: 99%